Implementasi Kurikulum dalam Meningkatkan Mutu Pendidikan Di SMK Negeri 1 Kota Blitar - Wahyudi, Imam (Proceedings Series of Educational Studies, 2025)
Curriculum Management has an important role in preparing the material that will be taught by the teacher, and also that will be learnt by the students. Curriculum can also be used as the parameter of the education quality and education succeed. This research tries to analyze and to find out the curricullum implementation to improve the educational quality in Vocational School One Blitar. This research uses qualitative approach , type of Case Study with multicases design. The result of this research shows, that the curriculum implementation in order to improve the education quality is done based on Process Standart, Teaching Official Decrees, teaching Scedule, competence test and National Test succeed Program, to point out homeroom Teacher, academic advisor, student's supervisor team and the last is a reward for the students also for the teacher that have some achievements.